O efeito da ação do fogo sobre a comunidade lenhosa da vegetação de Caatinga no refúgio de vida silvestre Pedra da Andorinha, Sobral, Ceará - Mariz, Amanda Freire (2024)
The Caatinga is a distinct phytogeographic domain in Brazil. Although it is located in tropical areas, it has a semi-arid climate, while most of the country has wetter climates. Due to rainfall concentrated in a few months, the Caatinga Domain is home to extensive areas of deciduous vegetation adapted to the seasonal climate. This region has historically been portrayed as an ecosystem poor in diversity and of great social poverty, but it is an area that is home to a wide biodiversity of animals and plants, many of which are endemic to the region, as well as considerable floristic heterogeneity. Despite this, the caatinga has historically suffered from several chronic disturbances, such as fires, overgrazing and deforestation, which have led several areas of the caatinga to suffer extreme degradation processes. The aim of this study was to analyze the effect of fires on the tree and shrub component of the Caatinga, and thereby seek to understand the impacts that this anthropogenic factor has on the ecosystem. This study was carried out at the Pedra da Andorinha Wildlife Refuge, located in the municipality of Sobral, state of Ceará. In 2018, three 50x50m plots were established, within which all woody plants with a diameter at ground level equal to or greater than 3 cm were recorded. In 2020, the reserve suffered from extensive anthropogenic fires, from a fire that originated in the area's surroundings and entered the plots. In order to assess the effects of fire on the diversity, structure and biomass of the vegetation, a new phytosociological survey was carried out in 2021 on the burnt plots. The initial pre-fire survey identified 704 woody individuals on 0.75 hectares, distributed among 21 species and 13 families. After the fire, the phytosociological survey recorded 536 individuals, distributed among 20 species and 12 families. The species Cordia oncocalyx and Combretum leprosum were more abundant in the pre- and post-fire surveys, although the number of individuals decreased. It was found that the incidence of this fire episode led to a reduction in the density and basal area of the community, with the mortality of 168 trees on 0.75 ha. Representatives of the species Cereus jamacaru, previously present in one of the plots, died as a result of the fire, slightly reducing species richness in the area. There was a reduction in biomass from 70,664 kg to 56,428 kg in the 0.75 ha after the fire, showing that the considerable loss of biomass in the Caatinga due to anthropogenic fires is detrimental to the structure of the vegetation and to biodiversity.